Eistla’s time-depth dive record overlaid with occurrences of type E and C signals. - Audra E. Ames (11349386); Susanna B. Blackwell (10013873); Outi M. Tervo (10013864); Mads Peter Heide-Jørgensen (7869812) (2021)
The top panel shows Eistla’s entire Acousonde record. Yellow dots represent type E calls, while black dots represent type C. In subpanels A-G, the x-axis is labeled with the start time and date of each panel, and each vertical interval represents two minutes. Panel A: Type E calls produced immediately following Eistla’s release. Panels B-C: A call and response exchange between type E and C. Panel D: Eistla returns from a ~230 m dive and five type E series (16 calls in the series) are produced while she lingers near the surface followed by one type C series (4 calls in the series). Panel E: One type E call followed by a type C response with type E signals continuing as Eistla leaves on a ~400 m dive. Panel F: Five type C series (14 calls in the series). Panel G: One type C response to a possible other whale (not featured in figure) followed by a type C series, two type C calls with a pulsed sound response (not featured in figured), a call and response exchange between type E and type C, and two type C series. Note that some signals are overlapped and therefore not all signals are clearly visible in the figure.